Molecular diversity of bla genes in Klebsiella pneumoniae and Escherichia coli isolates - Mendonça, Nuno Ricardo Furtado Dias (2009)
Dissertation presented to obtain a Ph.D. degree in Biology, speciality Microbiology, by Universidade Nova de Lisboa, Faculdade de Ciências e Tecnologia